Can Employee Turnover Intention Be Minimized through Job Satisfaction, Organizational Citizenship Behavior and Organizational Commitment? - Noermijati, Noermijati; Firdaus, Ema Zahra; Sulastri, Sulastri; Farhiya, Daniyatul (Universitas Brawijaya, Indonesia, 2024)
The greater the rate of employee turnover, the more harm it causes the company. Furthermore, there is a direct correlation between worker turnover and the intention to leave. Since the purpose of this research was to investigate employee turnover, the urgency of the issue is the main area of focus because it will obstruct the accomplishment of organizational objective. The purpose of this study is to examine the mediating role of organizational commitment and organizational citizenship behavior on the effect of job satisfaction on turnover intention. The research falls within the explanatory research category and included validation. This study utilised a survey to collect data from a significant portion of the workforce, consisting of 254 employees. The study used a saturated sample of 254 employees. The statistical method known as partial least squares, or PLS, along with the WarpPLS software were used for data analysis. The participants in this study were workers at an Indonesian manufacturer of medical devices. The research findings of this study provide an empirical contribution indicating that organisational commitment and organisational citizenship behaviour are critical components that need to be addressed in the company's efforts to lower the degree of intention to leave. Incorporating employees into decision-making processes can also help to maintain job satisfaction, as evidenced by the fact that such activities lower the intention of employee turnover. Companies should also focus on other factors that contribute to employee job satisfaction, such as clear career paths, appropriate rewards, work support facilities, and one example of good organisational citizenship on the part of employees not taking extra time off.